The use of generative artificial intelligence (AI) in Arabic language education: insights and implications between Malaysia and Indonesia - Sahrir, Muhammad Sabri; Albantani, Azkia Muharom; Arifin, Fatkhul; Fathudin, Fathudin (Research and Scientific Innovation Society, 2025)
Generative AI has emerged as a transformative tool in education, offering innovative solutions for Arabic language learning and teaching. This study explores the integration of generative AI technology in Arabic language education, focusing on its impact on student learning experiences and outcomes in Malaysia (IIUM) and Indonesia (UIN Jakarta). Examining AI’s role across five key dimensions—learning effectiveness, student engagement, accuracy in context understanding, learning adaptability and collaboration, and user acceptance and satisfaction—this study employed a quantitative survey involving over 500 undergraduate students between November and December 2024. Findings indicate that AI enhances learning effectiveness, engagement, and adaptability while addressing structural challenges in Arabic learning. However, limitations persist in AI’s contextual accuracy, cultural sensitivity, and ability to interpret idiomatic expressions. Future research should focus on refining AI’s cultural and linguistic sensitivity by integrating region-specific language models and collaborating with native Arabic educators to enhance accuracy, contextual awareness, and cultural appropriateness. Additionally, AI’s seamless integration with traditional teaching methodologies should be prioritized to ensure it serves as a complementary tool rather than a replacement in Arabic language education